Vespa Motorcycle Modification Effects to Increase Power and Torque - Bahtiar Wilantara; Haifan Nur Kholis; Edwin Yuliantoko; Hamid Nasrullah; Tombak Rizky Wijaya (Jurnal E-Komtek (Elektro-Komputer-Teknik), 2021)
This study aims to determine the effect of modifying the Vespa Sprint I-Get 150 ABS motorcycle on power and torque. The method used is to modify the intake manifold, combustion chamber, ignition, and exhaust channels. Power and torque were tested using the Bethar Racing Team Dunamometer. The test results show that: 1) modification of the piston from 58 mm to 66 mm increases engine capacity by 200.4 cc; 2) Modifications to the intake manifold, combustion chamber, ignition, and exhaust ducts can increase power by 24.8 hp at 5122 Rpm; 3) Modifications to the intake manifold, combustion chamber, ignition, and exhaust ducts can increase torque by 41.68 Nm at 1890 Rpm.